Decentralizing the Assessment Practice for Student Self-Learning - Rios-Munoz, D; Herrera-Araya, D (Emerson de Pietri, 2020)
This article aims to analyze assessment decentralization as a democratizing process driven towards strengthening student participation and learning. We have selected specialized literature from an interpretative perspective, considering the role of assessment agents, self-regulation of learning and assessment decentralization as review criteria. The central argument sustains that assessment decentralization consolidates reflexive, critical and self-critical practices associated with the learning processes. We conclude that consolidating self-assessment, co-assessment and peer assessment are fundamental in order to constitute evaluation as a space for negotiating meanings and inter-subjectivities that contribute in creating a culture of assessment that focuses on the progress of meaningful learning and the development of more self-aware students. © Emerson de Pietri.